Isotopic Evidence for Marine Consumption and Mobility in the Atacama Desert (Quillagua, Northern Chile). (12th March 2015) - Santana‐Sagredo, F.; Hubbe, M.; Uribe, M.
Abstract: Archaeological research in the Atacama Desert has recovered evidence of considerable cultural variability. This variability seems to have increased during the Late Intermediate Period (AD 950–1400). The oasis of Quillagua, located at the margins of the Loa River in northern Chile, between the Andes and the coast (70 km from the Pacific Ocean), has shown important evidence regarding this cultural diversity. The variety in the archaeological evidence found at Quillagua has been interpreted as the result of two different cultural influences at the oasis: the Pica‐Tarapacá who occupied the coastal and inland regions to the north of Quillagua and the Atacama who occupied the oasis and fertile areas southeast of Quillagua. Here, we present the results of stable carbon, nitrogen and oxygen isotope analyses of 23 individuals recovered from the Cementerio Oriente in Quillagua, in order to test whether the observed cultural variability is also reflected in diet and mobility patterns. Results from carbon and nitrogen isotope measurements indicate the importance of marine protein, as well as a contribution of maize in the diet of some individuals. Four individuals show low δ 18 O values, suggesting a possible highland or non‐local origin, whereas values for the remaining individuals are consistent with lowland populations. Together, the results support the idea that the Quillagua oasis represented an important site of interaction between the Tarapacá and Atacama cultures, with close contacts with the coast but also with the presence of individuals from the highlands. Copyright © 2015 John Wiley & Sons, Ltd.